The Influence of Financial Literacy, Locus of Control, and Fintech Payments on Personal Financial Management of Working Millennials in Pontianak City - Asep Nurzaman; Fuad Ramdhan Ryanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid advancement of financial technology, especially in fintech payment systems, has significantly shaped the financial behavior of millennials in Pontianak City—an age group that dominates the productive population and actively engages in digital financial services. This study investigates the impact of financial literacy, locus of control, and fintech payments on the personal financial management of employed millennials in Pontianak City. Using a quantitative approach with an associative research design, data were gathered through questionnaires administered to 150 purposively selected respondents and analyzed using multiple linear regression. The findings reveal that financial literacy, locus of control, and fintech payments collectively have a significant influence on personal financial management (F = 46.718; p = 0.000). In partial testing, financial literacy (t = 4.878; p = 0.000) and locus of control (t = 5.288; p = 0.000) exhibit positive and significant effects, while fintech payments show no significant impact (t = 1.333; p = 0.185). The coefficient of determination (R²) is 0.493, indicating that 49.3% of the variation in personal financial management can be explained by these three variables. These results underscore the crucial role of enhancing financial literacy and reinforcing self-control to promote sound financial management among millennials.